Eating up cognitive resources: Does attentional consumption lead to food consumption?. (1st July 2021) - Volz, Sarah; Ward, Andrew; Mann, Traci
Abstract: What is the role played by attentional load in eating? Does attending to an unrelated task generally lead to overeating, perhaps by preventing individuals from focusing on a goal to limit consumption? Or does such attentional diversion typically lead to reductions in eating, perhaps by preventing people from noticing tempting features of relevant food cues? Past research has supported each of these two propositions, but comparisons between existing studies have been hampered to the extent that various experimental manipulations differ in the degree to which they occupy attention, as well as differing in the particular type of attentional resources they exploit. To resolve existing discrepancies in the literature, in a series of studies, we made use of a working memory manipulation, the n-back task (Kirchner, 1958), that can be systematically modified to induce varying levels of cognitive load, allowing for rigorous comparisons of the effects of different levels of attentional load on eating. These studies revealed a complex pattern of results. Analysis of findings from three studies employing within-subjects designs documented a linear relationship, in that participants consumed less food when completing a higher cognitive-load task than when completing a lower cognitive-load task. Three studies employing between-subjects designs highlighted a less consistent pattern of results, but when combined in a mini-meta-analysis, suggested the opposite linear relationship, with participants assigned to higher cognitive-load conditions generally consuming more food than participants assigned to lower cognitive-load conditions. We conducted two additional studies to reconcile these conflicting patterns of data. Neither finding received unequivocal support, although both studies found that participants ate less when engaged in higher cognitive-load tasks than lower cognitive-load tasks. The precise nature of the relationship between attentional load and eating remains elusive.